Efficiency in the public sector : an analysis of performance measurements employed by the Western Cape Provincial Treasury - Bester, Albertus Viljoen (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2007.